ANALISIS KEGAGALAN SPHERICAL ROLLER BEARING PADA ROLL TABLE CONTINUOUS CASTING MACHINE - Titis Mudi Legowo Jati; Muhammad Anis Mustaghfirin; Bayu Wiro Kurniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Abstract – Failure on the bearing will cause a reduction in system accuracy, increased amplitudevibration or even failure on engine performance and produce unexpected consequences.In carryingout the analysis, the research method used in this study is an experimental quantitative researchmethod that is by simulating a spherical roller bearing model in ANSYS software to carry out stressdistribution analysis, deformation distribution and gravity load simulation that occur using staticstructural and Transient Simulation .From the results of static analysis using Static structural resultsin Annealed state, the maximum stress value is 4.8475 MPa, the total deformation value is 0.0001864mm and the force reaction value is 878.599 N. While the static calculation results of calculating inAnnealed state, the maximum value is obtained. stress is 5,343 MPa, total deformation value is0,000112 mm and force reaction value is 878,599 N and the results of dynamic analysis usingTransient dynamic in Annealed state obtained maximum stress value of 8,1951 MPa, totaldeformation value of 14,688 mm and force reaction value 6.31 x 10-7 N.